Metaphors Related to Climate Issues in @greenpeaceid’s Instagram: A Conceptual Metaphor Theory Approach - Adinda Maghfirah; Nurhayati Nurhayati; Tabita Eka Ayu Sofia (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
Climate change communication often relies on abstract and technical language, which makes environmental issues difficult for the public to understand and engage with. This study aims to examine how climate change is represented through conceptual metaphors in Instagram post texts published by @greenpeaceid, and how these metaphors shape public perception and emotional engagement. This study employs a descriptive qualitative approach. The research data consist of metaphorical expressions taken from Instagram post texts published by @greenpeaceid between 1 October and 30 November 2025, with a total of 135 posts selected through purposive sampling. The data were analyzed using the Metaphor Identification Procedure (MIP) to systematically identify metaphorical expressions, and further examined using Conceptual Metaphor Theory (Lakoff & Johnson, 1980) to analyze the mapping between source and target domains. The results show that 24 metaphorical expressions were identified, forming several dominant conceptual metaphors, including Nature Is A Body, Crisis Is A Person, and Ecosystem Is A Building. These metaphors represent environmental issues through familiar human experiences such as illness, danger, physical movement, and structural damage. Furthermore, the metaphors function to make abstract environmental problems easier to understand, create a sense of urgency and threat, evoke empathy and moral responsibility, criticize political systems indirectly, and encourage collective action. This study concludes that conceptual metaphors serve as an effective cognitive and communicative strategy in Indonesian environmental advocacy, particularly in digital contexts, by shaping how the public understands and emotionally responds to climate change.